THE PRESENCE OF LEARNING DRIVE AND NEEDS: AN EXPERIMENTAL STUDY OF THE CONTEXTUAL TEACHING AND LEARNING (CTL) MODEL IN ISLAMIC RELIGIOUS EDUCATION - Desma Hemaliyah Apita; A Gani; Didik Wahyudi; Baharudin (QANUN: Journal of Islamic Laws and Studies, 2025)
This study aims to examine the effect of the Contextual Teaching and Learning (CTL) instructional model on students’ learning motivation in the Islamic Religious Education (PAI) subject at SMP Negeri 3 Merbau Mataram. The research was prompted by the low level of students’ learning motivation, particularly in terms of learning drive and learning needs, which is attributed to conventional instructional practices that lack relevance to real-life contexts. The study employed a quantitative approach using a quasi-experimental design with a post-test only control group. The participants consisted of students from Class VIII A as the experimental group and Class VIII B as the control group. The data collection instrument was a Guttman scale-based learning motivation questionnaire, which had undergone validity and reliability testing. Data prerequisite tests included normality and homogeneity analyses, confirming that the data met the assumptions of parametric statistics. Data were analyzed using a pooled variance t-test at a 0.05 significance level. The results revealed a significant difference in learning motivation between students who received CTL-based instruction and those taught through conventional methods, as indicated by a Sig. (2-tailed) value of 0.023 < 0.05. These findings affirm that the CTL approach effectively enhances students’ motivation in learning PAI by offering more meaningful learning experiences closely related to real-life situations. Therefore, the implementation of the CTL model in PAI instruction is highly recommended to strengthen students’ intrinsic motivation and deepen their understanding of religious values.